The Principles of Layout and How Those Apply to Digital Electronic Book Publication - Yusuf Hendra Yulianto (Institut Seni Indonesia Yogyakarta, 2015)
When designing a layout, the designer must be aware of fundamental principles so as to make the design structured and consistent. When planning layout, a designer cannot be random and must consider essential factors, such as the media type, the readers, the design elements and so on. Electronic media, like web pages and electronic books, is a newer media than the print media, and is different in several aspects. Yet, the basic principles of the design are still identical. A solid layout is a great tool in communicating messages visually.